Efficacy of preoperative administration of single high dose intravenous tranexamic acid in reducing blood loss in total knee arthroplasty: A prospective clinical study - Turgut Akgül; Mehmet Büget; Ahmet Salduz; İpek S. Edipoğlu; Mehmet Ekinci; Süleyman Küçükay; Cengiz Şen (Acta Orthopaedica et Traumatologica Turcica, 2016)
Objective: The aim of this study was to analyse the effectiveness of single dose of 20 mg/kg intravenous tranexamic acid (TXA), in reducing the blood loss in patients undergoing total knee arthroplasty (TKA). Material and method: 70 patients (65.5 ± 8.1 years old) that have undergone TKA were divided in two groups. The 20 mg/kg IV TXA was given before the skin incision to one group (study group). On the control group, TKA was performed without TXA. The demographic data, body mass index, amount of bleeding and erythrocyte infusion during the operation, hemoglobin and hematocrit values (preoperative and 48th hour), the amount of drainage after the operation were compared between the groups. Results: The total amount of bleeding in the study group was 634.03 ± 182.88 ml and 1166.42 ± 295.92 ml in the control group (p < 0.001). Perioperative bleeding was 252.01 ± 144.13 ml in the study group and 431.33 ± 209.10 ml in the control group (p = 0.018). The drainage after the operation was 311.11 ± 141.64 ml at the 24th hour in the study group, 640.74 ± 279.43 ml at the 24th hour in the control group (p < 0.001). The drainage after 24th hour was 97.96 ± 115.86 ml in the study group and 112.96 ± 64.43 ml in the control group (p = 0.584). Conclusion: A high, single dose of TXA intravenously given to the patient prior to the TKA significantly reduces the bleeding during the operation and within the postoperative 24 h. There is no significant change in the bleeding amount after the 24th hour following the operation. Keywords: Total knee arthroplasty, Tranexamic acid, Postoperative bleeding, Peroperative bleeding